Rancang Bangun Sistem Informasi Surat Keterangan Pendamping Ijazah Studi Kasus STMIK Primakara - Soplantila, Joshael Junior; Wijaya, I Nyoman Yudi Anggara; Permana, Putu Trisna Hady (Jurnal Informatika, 2024)
Diploma Companion Certificate (SKPI) is a collection of student data that must be owned before graduating from university, in this letter various academic skills (soft skills) and non-academic skills (hard skills) are listed. Each university has the goal of creating the best graduates in certain fields so that they can become a benchmark for companies in recruiting their graduates. This SKPI is issued to complete the Diploma and Academic Transcripts. And is proof of having completed a certain level of education, and a transcript of a list of grades, achievements during lectures. SKPI describes the skills needed as prerequisites to compete in the world of work which can be seen from their academic background. The legal basis is the Regulation of the Minister of Education and Culture (Permendikbud) Number 81 of 2014 concerning Diplomas, Competency Certificates, and Higher Education Professional Certificates. In making this SKPI it can be said that it has not worked well because it has several weaknesses such as collecting data for each student in his achievements during the study process, therefore designing and building an information system to facilitate the performance of making this SKPI is needed. In designing the system build using the 4D learning device development method (define (definition), design (design), develop (development), disseminate (dissemination).